WEB APPLICATIONS USING MOTOR MATIC PHP AND MYSQL - Nur Ali Akbar; IRE Puspawardhani, SKom, MMSI IRE Puspawardhani, SKom, MMSI (Jurnal Sistem Informasi, 2010)
With the advancement of existing technology to support the creation of various typesof existing motor transportation. Currently matic motor became an option comparedwith other motor types. Because someone can be easier to ride and suitable for urban.TZT Racing garage that serves as the consumers who use motor matic. Providevarious services such as service, sales of motorcycle accessories matic.TZT matic motor racing website contains important information especially for peoplewho want to know about motor matic and its variations .. Various kinds ofaccessories and motor matic information described in this website, by displayingvarious pictures and articles based on the type-type variety and tips how to care maticmotor is good and right.